Turkish validity and reliability study of the psychological food involvement scale: PFIS-TR - İrem Nur Şahin; Aslıhan Atar; Özge Yaman; Halime Pulat Demir (BMC Psychology)
Abstract Background This study aimed to adapt the Psychological Food Involvement Scale (PFIS) to Turkish culture and test its validity and reliability. The PFIS measures individuals’ psychological, emotional, and social relationships with food, which significantly impact eating behaviors and health. Methods The study was conducted with 478 participants aged 18–65. The PFIS underwent a six-stage translation and cultural adaptation process. Data collection was carried out via Google Forms, with participants completing a general information form, PFIS, and the Addiction-like Eating Behavior Scale (ALEBS). Reliability was assessed using the test-retest method. SPSS 24 was used for statistical evaluation, including internal consistency coefficient calculations, factor analysis, and correlation tests. Results The Kaiser-Meyer-Olkin value was 0.94, indicating an adequate sample size, and Bartlett’s test of sphericity was significant (p < 0.05). Exploratory factor analysis revealed a four-factor structure explaining 79% of the variance, with factor loadings > 0.40 and eigenvalues > 1. Confirmatory factor analysis showed good fit indices: χ2 /sd = 2.28, GFI = 0.95, AGFI = 0.93 CFI = 0.98, NFI = 0.94, RMSEA = 0.05, SRMR = 0.04). Internal consistency analysis showed high reliability, with Cronbach’s Alpha coefficients ranging from 0.86 to 0.94 across subscales. Conclusion The Turkish version of the PFIS was found to be a valid and reliable tool for assessing psychological food involvement in the studied sample of the Turkish adult population.